A puncture-proof material and preparation method thereof

By blending tannin acid grafted copolymerized modified kaolin with ultra-high molecular weight polyethylene and carrying out specific process treatment, the problem of poor wear resistance of ultra-high molecular weight polyethylene fiber soft puncture-proof material is solved, and the material is efficient and puncture-proof and good breathability is achieved.

CN119161655BActive Publication Date: 2025-05-09RUIAN BOAN STAB RESISTANT MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411675956.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-05-09
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Ultra-high molecular weight polyethylene fiber soft anti-puncture materials have poor wear resistance during use, and have severe wear after long-term use, resulting in reduced material use effect.

Method used

By loading tannin acid on the surface of kaolin flakes and polymerizing with 2-acrylamido-2-methylpropanesulfonic acid and acrylic monomer under the action of an initiator, tanninic acid grafted copolymerized modified kaolin was obtained, which was then blended with ultra-high molecular weight polyethylene, and treated by melt blending extrusion, thermal drafting, relaxation and other processes to prepare puncture-proof materials.

Benefits of technology

It improves the hydrophilicity, water absorption and breathability of ultra-high molecular weight polyethylene fibers, while enhancing its puncture resistance and extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of fabrics, and specifically relates to a puncture-proof material and a preparation method thereof. The preparation method of the puncture-proof material comprises the following steps: placing kaolin in a ball mill, adding water glass and water for grinding, and obtaining kaolin flakes; adding kaolin flakes to water, adjusting the pH with N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid, adding tannic acid for stirring, obtaining tannic acid-modified kaolin and dispersing it in water, adding 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid to adjust the pH, and then adding an initiator for reaction after heating to obtain tannic acid graft copolymer modified kaolin; after uniformly mixing tannic acid graft copolymer modified kaolin with ultra-high molecular weight polyethylene, adding them to a twin-screw extruder, and obtaining the puncture-proof material through melt blending extrusion, heat drawing, and relaxation. The puncture-proof material has excellent moisture absorption and air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fabrics, and particularly relates to a puncture-proof material and a preparation method thereof. Background Art

[0002] In daily life, sharp objects such as blades are daily necessities that are difficult to be strictly controlled, which seriously threatens the safety of life and property of the people. Therefore, it is of great significance to strengthen the research and development of high-performance puncture-proof materials. At present, puncture-proof materials are mainly divided into hard puncture-proof materials, semi-hard puncture-proof materials and soft puncture-proof materials. In recent years, with the development of new materials and the improvement of people's requirements for wearing comfort, the research hotspot in the field of puncture protection has gradually shifted to soft materials, and high-performance fibers mainly based on para-aramid and ultra-high molecular weight polyethylene are increasingly used to develop soft puncture-proof materials. However, although soft puncture-proof materials can achieve very high strength, they often have problems with moisture absorption and poor air permeability.

[0003] Ultra-high molecular weight polyethylene fiber is a fiber spun from polyethylene with a molecular weight of 1 to 5 million. It is currently the fiber with the highest specific strength and specific modulus in the world. Due to its light weight, wear resistance, corrosion resistance, impact resistance, cut resistance, low temperature resistance, UV resistance, radiation resistance, and good biocompatibility, it plays an important role in modern warfare and aviation, aerospace, maritime defense equipment and other fields. However, in actual applications, it is found that the ultra-high molecular weight polyethylene fiber soft stab-proof material has poor wear resistance during use. After long-term use, it is severely worn, which greatly reduces the use effect of the ultra-high molecular weight polyethylene fiber soft stab-proof material. Based on the above background, it is necessary to conduct a deeper study on the performance of ultra-high molecular weight polyethylene fiber to promote its application. Summary of the invention

[0004] The first object of the present invention is to provide a method for preparing a puncture-resistant material, which is simple and easy to produce in practice.

[0005] The second object of the present invention is to provide a puncture-proof material having excellent moisture absorption and air permeability.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a puncture-resistant material comprises the following steps:

[0008] (1) Place kaolin in a ball mill, add water glass and water for grinding to obtain kaolin flakes;

[0009] (2) adding the kaolin flakes prepared in step (1) into water, adjusting the pH with N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid, and then adding tannic acid and stirring to obtain tannic acid-modified kaolin;

[0010] (3) dispersing the tannic acid-modified kaolin obtained in step (2) in water, adding 2-acrylamido-2-methylpropanesulfonic acid and acrylic acid, adjusting the pH, heating and then adding an initiator to react, thereby obtaining tannic acid graft copolymer-modified kaolin;

[0011] (4) The tannic acid graft copolymer modified kaolin obtained in step (3) is mixed evenly with ultra-high molecular weight polyethylene, and then added to a twin-screw extruder, and subjected to melt blending, extrusion, heat drawing, and relaxation to obtain a puncture-resistant material.

[0012] Furthermore, in step (2), the mass ratio of kaolin flakes to tannic acid is 1:(5-8).

[0013] Furthermore, in step (2), the stirring temperature is 65-75° C., the stirring time is 3-4 h, and the pH is adjusted to 8-9.

[0014] Furthermore, in step (3), the mass ratio of the tannic acid-modified kaolin obtained in step (2), 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, and initiator is 1:(3-6):(1-3):(0.002-0.004).

[0015] Furthermore, in step (3), the pH is adjusted to 7-8, the temperature after heating is 40-45° C., the initiator is composed of ammonium persulfate and sodium bisulfite in a molar ratio of 1:1, and the reaction time is 4-5 h.

[0016] Furthermore, the mass ratio of the ultra-high molecular weight polyethylene in step (4) to the tannic acid graft copolymer modified kaolin obtained in step (3) is 1:(0.05-0.2), and the average molecular weight of the ultra-high molecular weight polyethylene is 2.5-6.5 million.

[0017] Furthermore, in step (4), the screw speed of the twin-screw extruder is 100-120 rpm, the extrusion temperature is 160-180° C., the relaxation temperature is 120-140° C., and the relaxation multiple is 0.5-1 times.

[0018] Furthermore, the hot stretching in step (4) comprises three stretching steps in sequence, wherein the first stretching step has a stretching multiple of 3-4 times and a temperature of 90-100°C; the second stretching step has a stretching multiple of 2-3 times and a temperature of 100-110°C; and the third stretching step has a stretching multiple of 4-5 times and a temperature of 120-130°C.

[0019] Furthermore, in step (1), the mass ratio of kaolin, water glass and water is 1: (0.001-0.003): (4-7), and the grinding time is 3-5 hours.

[0020] A puncture-proof material is prepared by adopting the above preparation method.

[0021] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0022] 1. The present invention loads tannic acid on the surface of kaolin flakes, and then polymerizes tannic acid with 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid monomers under the action of an initiator to obtain tannic acid graft copolymer modified kaolin. The introduction of tannic acid, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid can not only increase the hydrophilicity of kaolin flakes, but also improve the compatibility of kaolin flakes with supermolecular polyethylene. The tannic acid graft copolymer modified kaolin obtained after the polymerization reaction is blended with supermolecular polyethylene. On the one hand, the hydroxyl and sulfonic acid groups in the tannic acid graft copolymer loaded by the kaolin flakes can improve the hydrophilicity and water absorption of supermolecular polyethylene fibers; on the other hand, the doping of kaolin flake nanoparticles and the porosity of kaolin itself effectively increase the porosity of supermolecular polyethylene fibers, which helps to improve the air permeability of the material. In addition, kaolin flakes as reinforcing fillers also improve the anti-puncture performance of supermolecular polyethylene fibers.

[0023] 2. The preparation method provided by the present invention has simple steps and is easy to implement and produce. The test results show that the material obtained by the preparation method of the present invention has good puncture resistance, air permeability and moisture permeability. DETAILED DESCRIPTION

[0024] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0025] 1. Embodiment

[0026] Example 1

[0027] Embodiment 1 provides a method for preparing a puncture-resistant material, and the specific preparation process is as follows:

[0028] (1) According to the mass ratio of kaolin, water glass and water of 1:0.002:6, kaolin was placed in a ball mill, and then water glass and water were added, and the mixture was ground for 4 hours, and then dried to obtain kaolin flakes;

[0029] (2) adding the kaolin flakes prepared in step (1) to water in a mass ratio of kaolin flakes to tannic acid of 1:7, adjusting the pH to 8.5 using N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid, adding tannic acid, and stirring at 70° C. for 3.5 h. After stirring, separating the product by suction filtration, repeatedly washing with water, and freeze-drying to obtain tannic acid-modified kaolin;

[0030] (3) According to the mass ratio of tannic acid-modified kaolin, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, ammonium persulfate-sodium bisulfite of 1:4.5:1.5:0.003, the tannic acid-modified kaolin obtained in step (2) is ultrasonically dispersed in water, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are added, and the pH is adjusted to 7.5 with sodium hydroxide solution. After heating to 42° C., an aqueous solution of ammonium persulfate and sodium bisulfite (molar ratio of 1:1) is slowly added dropwise, and the reaction is carried out for 4.5 hours. After the reaction is completed, it is dried to obtain tannic acid graft copolymer modified kaolin;

[0031] (4) According to the mass ratio of ultra-high molecular weight polyethylene to tannic acid graft copolymer modified kaolin of 1:0.08, the tannic acid graft copolymer modified kaolin obtained in step (3) and ultra-high molecular weight polyethylene (average molecular weight of 6 million) are mixed evenly, and then added to a twin-screw extruder, and the screw speed of the twin-screw extruder is set to 110 rpm and the extrusion temperature is set to 170°C. After melt blending and extrusion, three stretchings are performed in sequence, wherein the first stretching is 3.5 times and the temperature is 95°C; the second stretching is 2.5 times and the temperature is 105°C; the third stretching is 4.5 times and the temperature is 123°C. After hot stretching, relaxation treatment is performed, the relaxation temperature is 130°C, and the relaxation multiple is 1, to obtain a puncture-proof material.

[0032] Example 1 also provides a puncture-resistant material obtained by the above-mentioned preparation method.

[0033] Example 2

[0034] Example 2 provides a method for preparing a puncture-resistant material, and the specific preparation process is as follows:

[0035] (1) According to the mass ratio of kaolin, water glass and water of 1:0.001:4, kaolin was placed in a ball mill, and then water glass and water were added, and the mixture was ground for 3 hours, and then dried to obtain kaolin flakes;

[0036] (2) adding the kaolin flakes prepared in step (1) to water at a mass ratio of kaolin flakes to tannic acid of 1:5, adjusting the pH to 9 using N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid, adding tannic acid, and stirring at 65° C. for 4 h. After stirring, separating the product by suction filtration, repeatedly washing with water, and freeze-drying to obtain tannic acid-modified kaolin;

[0037] (3) According to the mass ratio of tannic acid-modified kaolin, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, and ammonium persulfate-sodium bisulfite of 1:6:3:0.002, the tannic acid-modified kaolin obtained in step (2) is ultrasonically dispersed in water, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are added, and the pH is adjusted to 7 using a sodium hydroxide solution. After the temperature is raised to 45° C., an aqueous solution of ammonium persulfate and sodium bisulfite (molar ratio of 1:1) is slowly added dropwise to react for 4 hours. After the reaction is completed, the tannic acid graft copolymer modified kaolin is obtained by drying;

[0038] (4) According to the mass ratio of ultra-high molecular weight polyethylene to tannic acid graft copolymer modified kaolin of 1:0.05, the tannic acid graft copolymer modified kaolin obtained in step (3) and ultra-high molecular weight polyethylene (average molecular weight of 2 million) are mixed evenly, and then added to a twin-screw extruder, and the screw speed of the twin-screw extruder is set to 100 rpm and the extrusion temperature is set to 180°C. After melt blending and extrusion, three stretchings are performed in sequence, wherein the first stretching is 3 times and the temperature is 90°C; the second stretching is 2 times and the temperature is 100°C; the third stretching is 4 times and the temperature is 120°C. After hot stretching, relaxation treatment is performed, the relaxation temperature is 120°C, and the relaxation multiple is 1 time, to obtain a puncture-proof material.

[0039] Example 2 also provides a puncture-resistant material obtained by the above-mentioned preparation method.

[0040] Example 3

[0041] Example 3 provides a method for preparing a puncture-resistant material, and the specific preparation process is as follows:

[0042] (1) According to the mass ratio of kaolin, water glass and water of 1:0.003:7, kaolin was placed in a ball mill, and then water glass and water were added, and the mixture was ground for 5 hours, and then dried to obtain kaolin flakes;

[0043] (2) adding the kaolin flakes prepared in step (1) to water in a mass ratio of kaolin flakes to tannic acid of 1:8, adjusting the pH to 8 using N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid, adding tannic acid, and stirring at 75° C. for 3 h. After stirring, separating the product by suction filtration, repeatedly washing with water, and freeze-drying to obtain tannic acid-modified kaolin;

[0044] (3) According to the mass ratio of tannic acid-modified kaolin, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, and ammonium persulfate-sodium bisulfite of 1:3:1:0.004, the tannic acid-modified kaolin obtained in step (2) is ultrasonically dispersed in water, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are added, and the pH is adjusted to 8 using a sodium hydroxide solution. After the temperature is raised to 40° C., an aqueous solution of ammonium persulfate and sodium bisulfite (molar ratio of 1:1) is slowly added dropwise to react for 5 hours. After the reaction is completed, the tannic acid graft copolymer modified kaolin is obtained by drying;

[0045] (4) According to the mass ratio of ultra-high molecular weight polyethylene to tannic acid graft copolymer modified kaolin of 1:0.2, the tannic acid graft copolymer modified kaolin obtained in step (3) and ultra-high molecular weight polyethylene (average molecular weight of 6.5 million) are mixed evenly, and then added to a twin-screw extruder, and the screw speed of the twin-screw extruder is set to 120 rpm and the extrusion temperature is set to 160°C. After melt blending and extrusion, three stretchings are performed in sequence, wherein the first stretching is 4 times and the temperature is 100°C; the second stretching is 3 times and the temperature is 110°C; the third stretching is 5 times and the temperature is 130°C. After hot stretching, relaxation treatment is performed, the relaxation temperature is 140°C, and the relaxation multiple is 0.5 times to obtain a puncture-proof material.

[0046] Example 3 also provides a puncture-resistant material obtained by the above preparation method.

[0047] 2. Comparative Example

[0048] Comparative Example 1

[0049] The difference between Comparative Example 1 and Example 1 is:

[0050] Omit steps (1)-(2);

[0051] Step (3) according to the mass ratio of tannic acid, 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid, ammonium persulfate-sodium bisulfite of 1:3:3:0.003, ultrasonically disperse tannic acid in water, add 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid, adjust the pH to 7.5, heat to 42°C, and then slowly dropwise add an aqueous solution of ammonium persulfate-sodium bisulfite (molar ratio of 1:1), react for 4.5 hours, and after the reaction is completed, dry to obtain a tannic acid graft copolymer;

[0052] In step (4), the tannic acid graft copolymer and the ultra-high molecular weight polyethylene (average molecular weight of 6 million) are uniformly mixed according to the mass ratio of the tannic acid graft copolymer to the ultra-high molecular weight polyethylene being 1:0.08, and the subsequent preparation process is consistent with that in Example 1.

[0053] Comparative Example 2

[0054] The difference between Comparative Example 2 and Example 1 is:

[0055] Steps (1) and (3) are omitted, and step (2) is the same as in Example 1;

[0056] Step (4) The tannic acid-modified kaolin and the ultra-high molecular weight polyethylene (average molecular weight of 6 million) are uniformly mixed according to the mass ratio of tannic acid-modified kaolin and ultra-high molecular weight polyethylene being 1:0.08, and the subsequent preparation process is consistent with that in Example 1.

[0057] Comparative Example 3

[0058] The difference between Comparative Example 3 and Example 1 is that:

[0059] Omit steps (1)-(3);

[0060] Step (4) Tannic acid and ultra-high molecular weight polyethylene (average molecular weight of 6 million) are uniformly mixed according to a mass ratio of tannic acid to ultra-high molecular weight polyethylene of 1:0.08, and the subsequent preparation process is consistent with that of Example 1.

[0061] Comparative Example 4

[0062] The difference between Comparative Example 4 and Example 1 is that:

[0063] Step (1) is the same as in Example 1, except that steps (2) to (3) are omitted;

[0064] Step (4) The kaolin flakes and ultra-high molecular weight polyethylene (average molecular weight of 6 million) are uniformly mixed according to the mass ratio of kaolin flakes to ultra-high molecular weight polyethylene of 1:0.08. The subsequent preparation process is consistent with that of Example 1.

[0065] 3. Test examples

[0066] Test Example 1

[0067] ① Cutting resistance

[0068] The cutting resistance test of the materials obtained in Examples 1-3 and Comparative Examples 1-4 was carried out using a test machine produced by Sodemat according to European standard EN388. The samples were placed on the cutting resistance tester, with aluminum foil placed underneath and moved horizontally. A spare circular blade was placed on the sample and rotated in the opposite direction (180 degrees) to the movement of the sample. °) rotates and moves forward, the two directions are opposite, when the sample is completely cut, the circular blade contacts the aluminum foil and is energized, at this time the circuit notifies the counter that the cutting is finished, the counter is always recording during the whole process; therefore, the cutting resistance data of the sample can be obtained. After the test, the cutting resistance level is based on the standard sample used (200g / m 2 The cutting level of the flat cotton fabric (of the same condition) is compared to evaluate. The test starts with the standard sample, and the test sample and the standard sample are alternately tested for cutting. After the test sample is tested 3 times, the standard sample is tested for the fourth time.

[0069] The calculation formula of the cutting resistance index is: N = (the counter reading value of the test sample before the test + the counter reading value of the test sample after the test)) / 2; Index = (the counter reading value of the test sample + N) / N

[0070] The level evaluation is classified by index in Table 1, and the test results are in Table 2.

[0071] ②Tensile strength

[0072] The tensile strength and tensile modulus of the materials obtained in Examples 1-3 and Comparative Examples 1-4 were tested on an LLY-06E single fiber strength tester. The interval between the upper and lower clamps was 20 mm, the tensile speed was 20 mm / min, the test temperature was room temperature, and each sample was tested more than 20 times. The results were averaged. The test results are shown in Table 2.

[0073] ③Impact strength

[0074] According to the method in GB / T1449-2005, the impact strength test was performed on the materials obtained in Examples 1-3 and Comparative Examples 1-4. The test results are shown in Table 2.

[0075] Table 1

[0076]

[0077] Table 2

[0078]

[0079] It can be seen from Table 2 that the materials obtained in Examples 1-3 have good anti-puncture performance. Compared with Examples 1-3, the anti-puncture performance of the materials obtained in Comparative Examples 1-4 is reduced to varying degrees, and the preparation process of the materials is adjusted in Comparative Examples 1-4. It can be seen from the above that changing the preparation method of the material of the present invention will affect the anti-puncture performance of the obtained material.

[0080] Test Example 2

[0081] The materials obtained in Examples 1-3 and Comparative Examples 1-4 were made into cloth and the performance was tested. The specific process is as follows:

[0082] I. Moisture permeability

[0083] According to GB / T 12704.2-2009 "Test method for moisture permeability of textile fabrics Part 2: Evaporation method", the moisture permeability of the fabrics made of the materials obtained in Examples 1-3 and Comparative Examples 1-4 was tested using a YG(B)216-II fabric moisture permeability meter. The experimental conditions were a temperature of 37°C and a relative humidity of 52%. Three circular specimens with a diameter of 70 mm were taken from each group of samples for testing. The results are the average of the test data of the three samples. The results are shown in Table 3.

[0084] II. Air permeability

[0085] According to GB / T 5453-1997 "Determination of Air Permeability of Textile Fabrics", the air permeability of the fabrics made of the materials obtained in Examples 1-3 and Comparative Examples 1-4 was tested using a YG(B)461D-Ⅰ digital fabric air permeability meter. The sample area of ​​each group of materials was 20 cm 2 , the pressure is 100Pa, each sample is tested 5 times, and the result is the average value of the 5 test data. The results are shown in Table 3.

[0086] Table 3

[0087]

[0088] It can be seen from Table 3 that the materials obtained in Examples 1-3 have good air permeability and moisture permeability. Compared with Examples 1-3, the air permeability and moisture permeability of the materials obtained in Comparative Examples 1-4 are reduced to varying degrees, and the preparation process of the materials in Comparative Examples 1-4 is adjusted.

[0089] Further analysis shows that the present invention loads tannic acid on the surface of kaolin flakes, and then polymerizes tannic acid with 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid monomers under the action of an initiator to obtain tannic acid graft copolymer modified kaolin. The introduction of tannic acid, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid monomers can not only increase the hydrophilicity of kaolin flakes, but also increase the compatibility of kaolin flakes with supermolecular polyethylene. The tannic acid graft copolymer modified kaolin is blended with supermolecular polyethylene. On the one hand, the hydroxyl and sulfonic acid groups in the tannic acid graft copolymer loaded by the kaolin flakes can improve the hydrophilicity and water absorption of the supermolecular polyethylene fiber. On the other hand, the doping of kaolin flake nanoparticles and the porosity of kaolin itself effectively increase the porosity of the supermolecular polyethylene fiber, which helps to improve the air permeability of the material. In addition, kaolin flakes (inorganic nanoparticles) as reinforcing fillers also improve the anti-puncture performance of supermolecular polyethylene fibers.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A method for preparing a puncture-resistant material, characterized in that: The following steps are involved: (1) Place kaolin in a ball mill, add water glass and water for grinding to obtain kaolin flakes; (2) adding the kaolin flakes prepared in step (1) into water, adjusting the pH with N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid, and then adding tannic acid and stirring to obtain tannic acid-modified kaolin; (3) dispersing the tannic acid-modified kaolin obtained in step (2) in water, adding 2-acrylamido-2-methylpropanesulfonic acid and acrylic acid, adjusting the pH, heating and then adding an initiator to react, thereby obtaining tannic acid graft copolymer-modified kaolin; (4) The tannic acid graft copolymer modified kaolin obtained in step (3) is mixed evenly with ultra-high molecular weight polyethylene, and then added to a twin-screw extruder, and subjected to melt blending, extrusion, heat drawing, and relaxation to obtain a puncture-resistant material; Wherein, the mass ratio of kaolin flakes to tannic acid in step (2) is 1:(5-8); In step (3), the mass ratio of tannic acid-modified kaolin obtained in step (2), 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, and initiator is 1:(3-6):(1-3):(0.002-0.004); The mass ratio of the ultra-high molecular weight polyethylene in step (4) to the tannic acid graft copolymer modified kaolin obtained in step (3) is 1:(0.05-0.2). The average molecular weight of the ultra-high molecular weight polyethylene is 2.5-6.5 million.

2. The method for preparing the puncture-resistant material according to claim 1, characterized in that: The stirring temperature in step (2) is 65-75° C., the stirring time is 3-4 hours, and the pH is adjusted to 8-9.

3. The method for preparing the puncture-resistant material according to claim 1, characterized in that: In step (3), the pH is adjusted to 7-8, the temperature after heating is 40-45° C., the initiator is composed of ammonium persulfate and sodium bisulfite in a molar ratio of 1:1, and the reaction time is 4-5 hours.

4. The method for preparing the puncture-resistant material according to claim 1, characterized in that: In step (4), the screw speed of the twin-screw extruder is 100-120 rpm, the extrusion temperature is 160-180° C., the relaxation temperature is 120-140° C., and the relaxation multiple is 0.5-1 times.

5. The method for preparing the puncture-resistant material according to claim 1, characterized in that: The hot stretching in step (4) includes three stretching steps in sequence, wherein the first stretching step has a stretching multiple of 3-4 times and a temperature of 90-100°C; the second stretching step has a stretching multiple of 2-3 times and a temperature of 100-110°C; and the third stretching step has a stretching multiple of 4-5 times and a temperature of 120-130°C.

6. The method for preparing the puncture-resistant material according to claim 1, characterized in that: The mass ratio of kaolin, water glass and water in step (1) is 1: (0.001-0.003): (4-7), and the grinding time is 3-5 hours.

7. A puncture-proof material, characterized in that: The preparation method is described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparationmethod of toughened and reinforcedpolymer composite material

    CN107057334A

  • Melt spinning preparation method of high molecular weight polyethylene fiber

    CN108588884A